Cooling with renewables: strategies for a green and efficient future - Muustafa Abdalla Othmam; Ail Dhaw Muftah Aljadi; Ahmed Saleh Ibrahim Mohamed (African Journal of Advanced Pure and Applied Sciences, 2025)
The global demand for cooling is rising rapidly due to population growth, urbanization, and climate change. Conventional cooling systems, which rely heavily on fossil fuels, contribute significantly to greenhouse gas emissions and energy inefficiency. This paper explores the potential of renewable energy sources to revolutionize the cooling sector, offering sustainable and efficient alternatives. By examining technologies such as solar-powered cooling, geothermal cooling, and bio-inspired designs, this study highlights strategies for integrating renewables into cooling systems. The paper also discusses policy frameworks, economic considerations, and future research directions to accelerate the adoption of green cooling solutions. The findings emphasize the urgent need for a transition to renewable-based cooling to mitigate environmental impacts and ensure energy security.